The Puzzling Relationship between Attention and Motivation: Do Motor Biases Matter? - Di Bello, Fabio; Giamundo, Margherita; Brunamonti, Emiliano; Cirillo, Rossella; Ferraina, Stefano (Neuroscience, 2019)
The relationship between attention and incentive motivation has been mostly examined by administering Posner style cueing tasks in humans and varying monetary stakes. These studies found that higher incentives improved performance independently of spatial attention. However, the ability of the cueing task to measure actual attentional orienting has been debated by several groups that have highlighted the function of the motor system in affecting the behavioral features that are commonly attributed to spatial attention. To determine the impact of motor influences on the interplay between attention and motivation, we administered 2 reaching versions of a cueing task to monkeys in various motor scenarios. In both tasks, a central stimulus indicated the reward stake and predicted the stimulus target location in 80% of trials. In Experiment 1, subjects were requested to report the detection of a target stimulus in each trial. In Experiment 2, the task was modified to fit a paradigm of Go/NoGo target identification. We found that attention and motivation interacted exclusively in Experiment 2, wherein anticipated motor activation was discouraged and more demanding visual processing was imposed. Consequently, we suggest a protocol that provides novel insights into the study of the relationship between spatial attention and motivation and highlights the influence of the arm motor system in the estimation of the deployment of spatial attention. •Incentive motivation improves monkeys' performance in cueing tasks by facilitating the reporting of target stimuli.•In reaching cueing protocols, motor preparation induces a (motivationally independent) validity effect.•An interaction between motivation and attention emerges when motor preparation is prevented.